Sigma Convergence Versus Beta Convergence: Evidence from U.S. County-Level Data - Andrew T. Young; Matthew J. Higgins; Daniel Levy (Bar-Ilan University, Department of Economics, 2003)
This note outlines (i) why σ-convergence may not accompany β-convergence; (ii) cites evidence of β-convergence in the U.S.; (iii) demonstrates that σ-convergence does not hold across the U.S., or within most U.S. states; and (iv) demonstrates the robustness of this finding to increases in mean income. The distributions of shocks appear important towards accounting for income disparity.
Keywords: O40; O11; O18; R11; 330; σ-convergence; β-convergence; Solow growth model; speed of convergence